Fracionamento geoquímico de metais em sedimentos e avaliação da qualidade da água do Rio Bento Gomes, Pantanal de Poconé, Mato Grosso - Coringa, Josias do Espírito Santo [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The sediment is a major compartments of aquatic ecosystems and can be used in assessing the level of contamination of those environments, because it organic compounds, pesticides, herbicides or inorganic trace elements as can be accumulated, reaching high concentrations. Its magnitude depends on the levels at which these metals are found in the river water, beyond the physical, chemical and biological processes that occur in its drainage basin. This work aimed to study the fractionation and availability of some trace elements in sediments of the Bento Gomes River, in Pantanal Poconé, Mato Grosso, and to evaluate the water quality of the watershed. For this purpose, sediment and water sampling were conducted in two distinct periods: in the dry season (August / 2012) and rainy (April / 2013). In the laboratory, the sediment samples were dried at controlled temperature of 45± 5 ° C., grinded, sieved and subjected to physical, chemical and mineralogical characterization. The levels of the metals Cr, Ni, Cu, Fe, Al, Zn and Mn were obtained by pseudo-total extraction techniques (3050B method by the Environmental Protection Agengy - EPA) and sequential extraction (BCR and Tessier methods), and readings metals by ICP-OES. The geochemistry of the sediment of Bento Gomes river is composed mainly of SiO2, followed by Al2O3, Fe2O3, K2O and MgO (in order). The high percentages of SiO2 and Al2O3 are generally related to the presence of chlorite and quartz in the mineralogical composition of the sediment. The pseudo total concentration of Cd, Cr, Cu, Mn, Fe and Zn in sediment had low levels not exceeding the guideline values of Resolution CONAMA nº. 454, in two seasonal periods, except for Ni, which achieved levels above the level -1 allowed the rainy season in one of the sampled points. By the procedures geochemical fractionation it was found that all the metals are present in significant concentrations in potentially mobilizable fractions...

O sedimento é um dos compartimentos mais importantes dos ecossistemas aquáticos e pode ser utilizado na avaliação do nível de contaminação desses ambientes, porque nele podem ser acumulados compostos orgânicos ou inorgânicos como elementos traços, alcançando concentrações elevadas. A magnitude depende da concentração em que esses metais se encontram nas águas dos rios, além dos processos físicos, químicos e biológicos que ocorrem em sua bacia de drenagem. Este trabalho teve por objetivo estudar o fracionamento e a disponibilidade de alguns elementos traços em sedimentos do Rio Bento Gomes, no Pantanal de Poconé, Mato Grosso, bem como avaliar a qualidade da água do manancial. Para tanto, foram realizadas amostragens de sedimentos e água em dois períodos distintos: na época da seca (agosto/2012) e chuvosa (abril/2013). Foram demarcados oito pontos de coleta de sedimento, localizados desde o cruzamento do Rio Bento Gomes com a Estrada Parque Poconé-Porto Cercado (MT-370). No laboratório, as amostras de sedimentos foram secas à temperatura controlada de 45 ± 5 °C., maceradas, peneiradas e submetidas à caracterização física, química e mineralógica. Os teores dos metais Cr, Ni, Cu, Fe, Al, Zn e Mn foram obtidos pelas técnicas de extração pseudo-total (pelo método 3050B da Environmental Protection Agengy - EPA) e sequencial (pelos métodos BCR e Tessier), e as leituras dos metais por ICP-OES. A água do rio Bento Gomes foi avaliada por meio da determinação de parametros físico-químicos e microbiológicos de acordo com a metodologia proposta no Standard Methods for the Examination of Water and Wastewater (APHA, 2012). A geoquímica dos sedimentos do Rio Bento Gomes é composta predominantemente por SiO2, seguido do Al2O3, Fe2O3, K2O e MgO (nesta ordem). Os teores elevados de SiO2 e Al2O3 geralmente estão relacionados com a presença da clorita e quartzo na composição mineralógica do sedimento. A...
Keywords: Química ambiental; Metais; Sedimentos fluviais; Decomposição quimica; Água - Qualidade; Metals